Structural And Failure Analysis Of Jib Crane Structure - et. al., B.Vikram, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main objective this project to analyze the strucutural capability of jib crane for different load conditon 0.5ton, 1ton, 2ton. Jib crane designed in soild work and FEA softwarwe used for static structural anaylizes, then results of deformation, equalant strees, strain and safty factore compared for given load condition